Artistic modelling of the screen chronotope in the cinema discourse - Галич, О. Б. (Studia Philologica, 2019)
The scientific investigation seeks to trace particularities of artistic modelling of time-and-space continuum in the cinema discourse. We maintained the precise description of the chronotope features of the historical context. The occurrence of such characteristics in narration appeared possible due to structural and semantic combination of categories of time, space and movement with temporythm being an integral part of the figurative text structure.